Public Participation’ Development in Trenggalek Regency’ Legal Drafting Through Support Budgeting - Kamalera S. T., Daniel Surya; Tjandra W., Riawan (European Scientific Journal, ESJ, 2018)
This paper focuses on explaining the idea of developing public participation in Trenggalek Regency’ legal drafting through support budgeting. The results of the study is based on the budgeting support’ model for the participation of the public through the Region Revenues and Expenditures Budget (APBD) which was further analyzed through the theory of participation and the theory of law enforcement. The results show that support budgeting is still centered on the activities of regulators and has not yet created a budgeting system that is aimed specifically towards the development of public’ participation. There has not been a good application yet of the theory of participation and the theory of law enforcement in the preparation of APBD. This, however, is attributed to the fact that the budget system has not fully supported the development of Public participation in the regional regulations’ drafting. This problem can be solved with a good and same understanding about the meaningful Public participation in the regional regulations’ drafting among the regulators.